Changes in homocysteine and 8-iso-PGF2a levels in football and hockey players after a match - Papapanagiotou, A.; Gissis, I.; Papadopoulos, C.; Souglis, A.; Bogdanis, G. C.; Giosos, I.; Sotiropoulos, A. (Research in Sports Medicine, 2011)
The aim of the present study was to evaluate the levels of homocysteine and 8-iso PGF2a in football and hockey players before and soon after a match, on the predisposition for development of atherosclerosis. We measured 8-iso-PGF2a and homocysteine in 21 football athletes aged 21.8 ± 3.7 years old and 18 hockey athletes 22.2 ± 3.3 years old, respectively. All the athletes presented significant increases in serum homocysteine levels following the match (p = 0.001 for football and p = 0.001 for hockey players) Also a statistically significant increase of 8-iso-PGF2a levels was found in hockey and football athletes following the match (p < 0.001 and p = 0.071). Our findings suggest that strenuous exercise such as a football or a hockey match causes a marked increase in serum homocysteine and 8-iso-PGF2a. Due to the fact that homocysteine and 8-iso-PGF2a are contributing to atheromatosis, it may be useful to follow a restoration exercise program that involves mild exercise and to pay special attention to folate, vitamin B6, and vitamin B12 balance during the first 24 h after the match.